Development of learning media for physical education, sports, and health on basic football techniques based on articulate storyline application - Rika Navi’atul Khasanah; Hariyoko Hariyoko (Universitas Negeri Malang, 2023)
The purpose of this research is to develop PJOK learning media in the form of interactive multimedia in the form of the Articulate Storyline application. So, it is hoped that through the development of this learning media it can help and make it easier for PJOK teachers in high schools to convey basic football technical material in an interesting way and help students understand basic football technical material easily. This study uses development research methods with data obtained in the form of qualitative and quantitative data. The results showed that the average value obtained from the validation of football learning experts was 89%, the validation of learning media experts was 96.2%, the PJOK expert validation was 89.4 and product trial was 87,7%. From this research, it can be concluded that the learning media for basic football technique material based on the Articulate Storyline application for class XI students at State Senior High School 2 Batu is feasible to be applied without any revision.